The association and impact of radiographic, pathological emphysema and spirometric airway obstruction on patients with resectable lung adenocarcinoma - Yixiao Zhang; Lu Lang; Xiaojuan Guo; Kewu Huang; Jiawen Yi; Yuan Yuan; Min Zhu; Shu Zhang; Bin Hu; Xue Li; Yuhui Zhang (Respiratory Research)
Abstract Background Destruction of alveoli structure and lung function are interrelated, however, their correlation and clinical significance have been not well defined in patients with lung cancer. Thus, this study aimed to examine the association among radiographic, pathological emphysema and spirometric airway obstruction in patients with resectable lung cancer as well as explore their impact on postoperative pulmonary complications (PPCs) and long-term prognosis. Methods Lung adenocarcinoma (LUAD) patients who performed chest CT, spirometry, and curative resection were included from a prospective three-institution database. CT-defined emphysema at baseline was assessed visually and quantitatively, pathological emphysema was reviewed on postoperative specimen. Multivariable regression models, propensity score matching, stratified analysis, and subgroup analysis were adopted to reduce selection bias. Results Our cohort included 902 patients, with a median follow-up of 5.6 years. CT-defined emphysema was present in 163 patients (18.1%) and most of them (86.5%) were validated with pathological evidence. 169 had spirometric airway obstruction, while only 29.6% patients overlapped with CT-defined emphysema. Multivariable logistic regression models showed CT-defined emphysema, not airway obstruction, was associated with an increased risk of PPCs (adjusted odds ratio, 2.35; 95% CI, 1.40–3.93; P = 0.001). After adjusting for age, sex, body mass index, smoking history, tumour stage, vascular invasion, pleural invasion, multivariate cox analysis identified CT-defined emphysema, not airway obstruction, as an independent prognostic factor for OS (adjusted hazard ratio, 1.44; 95%CI, 1.05–1.97; P = 0.022). Patients with both radiographic and pathological emphysema experienced worse OS (log-rank P < 0.001). In the propensity score-matched cohort, stratified analysis, and never-smokers subgroup analysis, CT-defined emphysema remained a strong and statistically significant factor related to poor survival. Conclusions The presence of radiological and pathological emphysema in resectable LUAD was associated with frequent PPCs and decreased survival. Clinical trial number Not applicable.